2011
DOI: 10.1097/sla.0b013e318204e637
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for Lymph Node Yield in Colon Cancer Resection Specimens

Abstract: Multiple tumor and surgical factors are associated with lymph node yields in colon specimens. A standard minimum of lymph nodes may not be applicable to all colon cancer resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
57
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 11 publications
11
57
1
Order By: Relevance
“…Each factor likely influences the LN sample to a modest, yet significant, degree, as demonstrated by the multivariable modeling in this series. This observation is in accordance with a previous study, in which four factors collectively explained 19% of the overall variation in the prediction model (35). Genetic features should be considered together with other clinicopathological factors when assessing node count after surgery for colon cancer.…”
Section: Resultssupporting
confidence: 78%
“…Each factor likely influences the LN sample to a modest, yet significant, degree, as demonstrated by the multivariable modeling in this series. This observation is in accordance with a previous study, in which four factors collectively explained 19% of the overall variation in the prediction model (35). Genetic features should be considered together with other clinicopathological factors when assessing node count after surgery for colon cancer.…”
Section: Resultssupporting
confidence: 78%
“…In addition to localization by PCT, several authors recently reported that PCT could increase the number of nodes examined [6][7][8]. The reason for increased lymph node yield after tattooing was attributed to the fact that India ink-containing lymph nodes can be more easily detected by the surgeon or pathologist (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Age, tumor size, depth of penetration, location, use of radiation, and gene mutations have been associated with lymph node yield. 4,[7][8][9] These findings suggest a host-tumor interaction that may result in stimulation of the immune system and, as a consequence, larger and thus easier to identify mesenteric lymph nodes. It does not stretch the imagination to consider that such an interaction would have implications for tumor recurrence.…”
mentioning
confidence: 94%
“…Many protocols have been advocated to maximize nodal yield, including the use of in vivo or ex vivo dye injection, fat clearance, and multiple rounds of gross examination. [4][5][6] However, one cannot categorically state that specific surgical or pathologic methods are necessary to achieve such yields in all cases, because this has not been adequately studied in a prospective, controlled fashion.…”
mentioning
confidence: 99%
See 1 more Smart Citation